Tinjauan Histori pada Gaya Visual Iklan Cetak Coca-Cola - Nadia Sigi Prameswari (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2020)
Zeitgeis (the soul of the times) has a great influence on the characteristics of works of art in the form of paintings, sculptures, reliefs, illustrations, writing to develop into advertisements. Advertising is one of the works of art that appeared in the 17th century. In the 1880s, several manufacturers or companies adapted the techniques by which advertisements appeared on posters. Various producers of food, beverage, medicine and toiletries began to introduce their products through poster advertisements. In 1886, The Coca-Cola Company was founded in America. In 1906, William D'Arcy joined as the Creative Team that planned the Coke advertising concept and had the view that